Use of soil microorganisms as a biotechnological strategy to enhance avocado (persea americana)-plant phosphate uptake and growth / uso de microorganismos del suelo como estrategia biotecnológica para mejorar la absorción de fósforo y el crecimiento (2012)
In recent years the area cultivated with avocado has increased significantly in Colombia and this trend is expected to continue in the coming years. However, most of the soils in the highlands of the Colombian Andean, that have been used to grow avocado, are strongly acidic and nutrient deficient, particularly phosphorus (P). To alleviate these problems, high rates of lime and P fertilizers are frequently applied, in many cases the applied dose are excessive. This increases production costs, produces plant nutrient imbalance in the plant, and increases the risk of polluting surface waters. A biotechnological alternative is the combined use of phosphate solubilizing microorganisms (PSM) and arbuscular mycorhizal fungi (AMF). This work describes a series of experiments carried out to isolate, characterize, and evaluate the effectiveness of AMF and PSM in increasing plant growth and P uptake of avocado plants. The results indicate that the mycorrhizal association is an effective alternative that can easily be established in the crops; however, the excessive use of P fertilizer in these soils may limit the benefits of these fungi on avocado plants. Currently, effective PSM of avocado rhizosphere have not been detected. In some cases, these microorganisms are absent in the avocado rhizosphere and in other cases their low capacity to solubilize P discourage their use in the crop. / En los últimos años el área cultivada con aguacate en Colombia ha crecido notoriamente y se espera que esta tendencia continúe en los próximos años. Sin embargo, muchos de los suelos de la zona andina utilizados para su siembra exhiben fuerte acidez y niveles deficientes de varios nutrientes, particularmente fósforo (P). Para corregir este problema se hacen aplicaciones de cales y fertilizantes fosfóricos solubles, en mucho casos las dosis aplicadas son altas. Esto eleva innecesariamente los costos de producción, crea desbalance nutricional en la planta y genera riesgos de contaminación ambiental. Una alternativa biotecnológica es el uso de microorganismos solubilizadores de fosfato (PSM) y hongos formadores de micorriza-arbuscular (AMF). En este trabajo se describe el aislamiento, caracterización y evaluación de la efectividad de AMF y PSM para mejorar la absorción de P por las plantas de aguacate. La asociación micorrizal ha probado ser una alternativa factible de implementar; sin embargo, el excesivo uso de fertilizantes fosfóricos puede limitar los beneficios de estos hongos en las plantas de aguacate. Hasta ahora no se han detectado PSM efectivos en la rizosfera de aguacate. En algunos casos, estos microorganismos están ausentes en la rizosfera del aguacate, y en otras circunstancias la baja capacidad para solubilizar P desestimula su uso en el cultivo.